2018
DOI: 10.1016/j.canlet.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Targeting immuno-metabolism to improve anti-cancer therapies

Abstract: The immunology community has made significant strides in recent years in using the immune system to target and eliminate cancer. Therapies such as hematopoietic stem cell transplantation (HSCT) are the standard of care treatment for several malignancies, while therapies incorporating chimeric antigen receptor (CAR) T cells or checkpoint molecule blockade have been revolutionary. However, these approaches are not optimal for all cancers and in some cases, have failed outright. The greatest obstacle to making th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 115 publications
0
13
0
Order By: Relevance
“…Based on recent discoveries in the field of cancer metabolism that we discussed previously, researchers have proposed new rationales behind cancer metabolism, providing insight into why XRT and immune therapy are perhaps the best clinically available weapons we have to fight cancer. Very little effort has been directed toward tackling the metabolic aspect of cancer using radiation and addressing targeting of immune metabolism to improve cancer therapies (77). XRT is the only effective established clinical tool that takes advantage of the metabolic aspect of cancer.…”
Section: Xrt: Challenging the Tumor Stroma And Tmementioning
confidence: 99%
“…Based on recent discoveries in the field of cancer metabolism that we discussed previously, researchers have proposed new rationales behind cancer metabolism, providing insight into why XRT and immune therapy are perhaps the best clinically available weapons we have to fight cancer. Very little effort has been directed toward tackling the metabolic aspect of cancer using radiation and addressing targeting of immune metabolism to improve cancer therapies (77). XRT is the only effective established clinical tool that takes advantage of the metabolic aspect of cancer.…”
Section: Xrt: Challenging the Tumor Stroma And Tmementioning
confidence: 99%
“…Second- and third-generation CAR-T cells include the expression of costimulatory molecules, such as CD28 or 4–1BB (CD137), which together with the receptor can dramatically improve antitumor activity. The effect of the co-stimulation is not limited to the immune signalling mediated by these co-receptors, but they can also differentially influence cellular metabolism favouring cellular fitness and improve both effector function and persistence of the CAR-T cell (189192). …”
Section: Mitochondrial and Fatty Acid Metabolism In Human Immune Respmentioning
confidence: 99%
“…The effect of the costimulation is not limited to the immune signaling mediated by these co-receptors, but they can also differentially influence cellular metabolism favoring cellular fitness and improve both effector function and persistence of the CAR-T cell. [189][190][191][192] In particular, it has been found that co-stimulation through 4-1BB is associated with a longer survival and enhanced memory development when compared to CAR-T cells expressing CD28. 189,192 Interestingly, 4-1BB-expressing cells were also characterized by enhanced mitochondrial biogenesis and metabolism, higher SRC and rates of FAO, as well as a differential expression of metabolic genes favoring FA metabolism over glycolysis, including Cpt1a and Fabp5.…”
Section: Treatment Of Naive or Cd28 + Memory Cells With The Foxo1 Inhmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, preserved cytotoxicity results from a preservation in cytokine responses in remaining T cells ( 70 ), coupled with a decrease in T cell dysfunction due to lower rates of GVHD ( 97 ). In other cases, better tumor control may result from the dual impact of metabolic modulation on both alloreactive T cells and the underlying malignancy ( 98 , 99 ). It has also been argued that T cell activation, and hence metabolic demands, operate on a continuum, with GVHD-causing T cells at the far end of the activation and metabolic spectrum ( 100 ).…”
Section: Effects Of Metabolic Inhibition On Graft-vs-tumor Responsesmentioning
confidence: 99%